2009
DOI: 10.1080/15563650601117954
|View full text |Cite
|
Sign up to set email alerts
|

Acute topiramate overdose – clinical manifestations

Abstract: The clinical manifestations of acute poisonings with topiramate ranged from asymptomatic to severe, but no distant sequelae or fatalities were observed. The course of acute poisoning seems to be more severe in patients who were not previously treated with topiramate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…The most prevalent side effects of topiramate are CNS effects such as psychomotor slowing, cognitive impairment, dizziness, ataxia, and behavioural changes [13][14][15][16]. Adverse events and encephalopathic features may become prominent at plasma concentrations >20 mg/L [12].…”
Section: Introductionmentioning
confidence: 98%
“…The most prevalent side effects of topiramate are CNS effects such as psychomotor slowing, cognitive impairment, dizziness, ataxia, and behavioural changes [13][14][15][16]. Adverse events and encephalopathic features may become prominent at plasma concentrations >20 mg/L [12].…”
Section: Introductionmentioning
confidence: 98%
“…It is indicated as a monotherapy or adjunctive therapy to alleviate partial seizures, generalized tonic-clonic seizures, and Lennox-Gastaut syndrome. Topiramate is also being used in the treatment of migraines, cluster headaches, essential tremors, binge eating disorders, acute mania, Tourette's syndrome, neuropathic pain, bipolar disorder, alcohol dependence, excess body weight, and smoking (4,5). Structurally, topiramate is unrelated to other anticonvulsants and acts by multiple neurostabilizing processes (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…A 17 year old lady with suicidal intake of 800 mg of topiramate developed incoherence, confusion, disorientation, and speech impairments, but eventually had full resolution of symptoms within ~24 hours [10]. Most patients with topiramate toxicity recover relatively quickly with just supportive treatment [4,5,10,11,13]. In our literature search we found only two cases of fatal topiramate toxicity.…”
Section: Discussionmentioning
confidence: 81%
“…Less commonly a variety of gastrointestinal symptoms have also been described [6]. Several reports describe toxicity at varying doses of ingestion when used for migraine and epilepsy (Table 2) [4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Based on a retrospective review of 567 cases of topiramate toxicity (during 2000-2001), the American Association of Poison Control revealed that: 39% were adults, mild mental status changes were common, and severe respiratory depression or persistent NAGMA were infrequent yet other reports confirm their occurrence [5,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation